Penguatan Pendidikan Antikorupsi Perspektif Esensialisme: Penguatan Pendidikan Antikorupsi Perspektif Esensialisme - Sumaryati, Sumaryati; Murtiningsih, Siti; Maharani, Septiana Dwi Putri (Integritas : Jurnal Antikorupsi, 2020)
Indonesia scored 40 points out of 100 and ranked 85th out of 180 surveyed countries on the 2019 Corruption Perceptions Index (CPI). One of the efforts to increase the index score is by preventing corruption, including through anti-corruption education. Anti-Corruption Education has a strategic role in preventing corruption, so efforts are needed to strengthen it. This article examines the strengthening of Anti-Corruption Education from the perspective of essentialism, namely the periodic review of material by all stakeholders, the strengthening of concepts and methodologies, the formulation of values hierarchies, strengthening the synergy of chess center education, the formulation of scientific fields, and community cultural reform. The conclusion is that the Corruption Eradication Commission and stakeholders must conduct regular Anti-Corruption Education material reviews; recommend scientific to the Indonesian Ministry of Research and Technology for Higher Education as the implementation in Higher Education; and every educational institution strengthens with the Anti-Corruption Literacy Movement and/or the formation of extracurricular Anti-Corruption Student Communities.